ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN NASABAH UNTUK MENGAMBIL PEMBIAYAAN PADA KOSPIN JASA LAYANAN SYARIAH PEKALONGAN - Jatun, Rengganing; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2015)
Distribution of funds in the conventional system known as financing, financing cooperative given based not only a relationship between finance and the debtor but to establish a partnership. Problems in this study was a decrease in the number of customers who take out financing Kospin Jasa SyariahÂ Pekalongan. It can be quite detrimental to health cooperative of the cash flow, because customers save more than customers who took the financing, so that existing funds can not be channeled properly. The purpose of this study was to analyze the effect of product knowledge, promotional activities, and religiosity of the customer in making financing decisions. This research is quantitative research. The sample used in this study were 88 members Kospin Jasa Syariah Pekalongan customers using accidental sampling technique. The data used is primary data by questionnaire. The analysis technique used is quantitative analysis using multiple regression analysis. According to the research done can be seen that the product knowledge, promotional activities and religiosity positive effect on the customer's decision took financing. Based on the results of testing goodness models, regression models can be used to predict a customer's decision took financing. While customers take financing decisions can be explained by three variables: product knowledge, promotional activities, and religiosity of 85.6%.